The Impact of Patriarchal Practices on Cassie Hanwell in Things You Save in a Fire - Felicia; Mau, Emanuella Christine Natalia (International Dialogues on Education Journal, 2022)
This research examined a literary work titled Things You Save in a Fire, written by Katherine Center. The novel tells the story of a female firefighter named Cassie Hanwell who faces sexual assault and workplace gender discrimination. There were two research questions addressed in this study. The first question aimed to find the depiction of patriarchal practices in the novel, namely the sexual assault and workplace gender discrimination experienced by Cassie Hanwell. The second question examined the impact of sexual assault and workplace gender discrimination on Cassie Hanwell. This literary analysis applied a qualitative research approach by selecting and grouping the data for analysis. To answer the two research questions, theories of patriarchy, feminism, character, and characterization were applied. The data sources were books and journal articles. The results of the study showed the impact of patriarchal practices on Cassie Hanwell. After the sexual assault and gender discrimination at the workplace, Cassie becomes lonesome and skeptical. She also turns into a paranoid and aggressive person and suppresses her feelings.